ТЕНЗОЭЛЕКТРИЧЕСКИЕ СВОЙСТВА КРЕМНИЯ С НАНОКЛАСТЕРАМИ АТОМОВ МАРГАНЦА - Камалов, А.Б.; Жалелов, М.А.; Турсынбаев, С.А. (SCIENCE and SOCIETY, 2023)
It was found that, in contrast to conventional semiconductor materials, silicon with nanoclusters of manganese atoms exhibits a high tens sensitivity at room temperature, which is difficult to explain by the existing theory. The high tens sensitivity in the obtained material is associated with the changing of state of nanoclusters of manganese atoms in the presence of pressure. These data show that silicon with nanoclusters of manganese atoms can serve as a promising material for creating a new class of strain gauges. By controlling the concentration and charge state of nanoclusters of manganese atoms, one can change the tens sensitivity of the obtained material.
Keywords: semiconductor; pressure; nanocluster; strain gauge; manganese; diffusion